Psychological and Pedagogical Basis of Teaching Colors to Primary Class Students - Abdullazizova Rokhatoy Usmonaliyevna (Open Academia, 2023)
The article presents a linguistic analysis of the linguistic landscape of the world and a general interpretation of the concept of "Landscape of the World". Also, the proportionality of the linguistic landscape of the world in different languages, its introduction into Uzbek linguistics, linguistic relativity, the influence of linguistic culture on the linguistic landscape of the world, and several functions of the concept of the linguistic landscape of the world were studied.